Atorvastatin influence on cardiac function and rhythm variability in patients with chronic lymphocytic leukemia in remission - B. B. Samura (Zaporozhye State Medical University, 2019)
Purpose - to evaluate atorvastatin influence on cardiac hemodynamics and rhythm variability in patients with chronic lymphocytic leukemia (CLL) in remission. Materials and methods. One hundred fifty-seven subjects with chronic lymphocytic leukemia in full or partial remission were enrolled in the study. Atorvastatin at doses 20 mg/d and 40 mg/d were prescribed for patients with hypercholesterinemia, dyslipidemia, coronary artery disease risk factors. All patients and control subjects underwent echocardiography, and 24-hour Holter monitoring with continuous time-dependent and spectral analysis of heart rate variability at baseline, after 1 year and after 3 years of observation period. Cardiovascular events were evaluated for 3 years observation period. Results. In one year after reaching remission of CLL in comparing with baseline there is a statistical decrease in E (0.98 ± 0.15 м/с and 0.89 ± 0.16 м/с; P < 0.001), A (0.98 ± 0.16 м/с and 0.92 ± 0.15 м/с; p=0.023). E/A (P = 0.011) were significantly lower in group of patients without atorvastatin treatment (P = 0.011) and in group treated with atorvastatin in dose 20 mg a day (P = 0.002). In three year EF decreased in comparing with baseline (55.43 ± 4.75 % and 51.52 ± 6.40 % і; P = 0.009) in patients without atorvastatin treatment. In three year global circular systolic strain (-17.42 ± 3.24% and -16.78 ± 3.56 %; P = 0.035), global longitudinal systolic strain (-18.13 ± 2.15 % and -17.04 ± 2.07 %; P = 0.008), global longitudinal systolic strain rate (-1.03 ± 0.23с-1 and -0.91 ± 0.33с-1; P = 0.024) were significantly decreased in patients without atorvastatin treatment. The LF values of group of patients treated without atorvastatin of patients were significantly lower than those of controls, and HF values of patients with CLL (P = 0.043) and HNL (P = 0.04) were lower. Conclusions. Among patients with chronic lymphocytic leukemia in remission systolic and diastolic function, regional systolic contractility and variability of cardiac rhythm were significantly worse in three year especially in patients without atorvastatin treatment.